Association of LXRα polymorphisms with obesity and obesity-related phenotypes in an Iranian population. (May 2014) - Rooki, Hassan; Ghayour-Mobarhan, Majid; Pourhosseingholi, Mohamad-Amin; Azarpazhooh, Mahmoud-Reza; Ebrahimi, Mahmoud; Ferns, Gordon; Zali, Mohammad-Reza
Abstract Background: Obesity is a multifactorial disorder due to the complex interaction between genetic and environmental factors. Liver X receptor alpha (LXRα), encoded by the gene NR1H3, is involved in lipoprotein metabolism and its genetic variations may also play a role in the aetiology of obesity. Aim: To assess the association of two NR1H3 polymorphisms (rs11039155 and rs2279238) and their haplotypes with obesity in an Iranian population. Subjects and methods: A total of 447 unrelated subjects (including 206 overweight, 162 obese and 79 controls) were enrolled in the study and were genotyped by TaqMan assay using DNA from peripheral blood. The association of these two LXRα polymorphisms with the presence of obesity and overweight was assessed. Results: There was no significant association between the two SNPs and obesity, even after adjustment for age and sex. By logistic regression using a dominant model, the odds ratios for obesity were: 1.32 (0.85–2.74) for rs11039155 and 0.77 (0.30--1.99) for rs2279238. Haplotype analyses identified three common haplotypes GC, GT and AC with frequency greater than 1%, but none of the haplotypes was associated with the risk of obesity. Conclusions: This study revealed that there was no significant association between LXRα polymorphisms and the presence of obesity in an Iranian population and suggests that these two SNPs are not major contributors to obesity risk in this population.